A cell‐centric view of lung alveologenesis. Issue 4 (17th November 2020) - Vila Ellis, Lisandra; Chen, Jichao
Abstract: Lung alveologenesis, formation of the alveolar region, allows sufficient gas exchange surface to be packed inside the chest cavity yet with orderly connection to the trachea. The real‐life alveolar region, however, bears little resemblance to idealized cartoons owing to its three‐dimensional nature, nonuniform shape, and mostly air‐filled void. This morphological complexity is matched by its cellular complexity—comprised of intermixed and often tangled cells of the epithelial, mesenchymal, endothelial, and immune lineages. Modern imaging, genetics, and genomics are shedding light on and updating traditional views of alveologenesis. Accordingly, this review describes a cell‐centric 3‐phase definition of alveologenesis and discusses its failure in diseases and possible reactivation during regeneration. Key Findings: We propose a cell‐centric 3‐phase definition of lung alveologenesis to account for the morphological ambiguity of alveoli. The initial alveologenesis phase begins with alveolar type 1 cell flattening and forms alveolar ducts and alveolar sacs. The classical alveologenesis phase is marked by alveolar myofibroblasts. The continued alveologenesis phase increases alveolar surface and outpocketing in the absence of alveolar myofibroblasts. A distinct Car4 endothelial cell population demarcates and is required for alveolar outpocketing, and may underlie intussusceptive angiogenesis but does not support the model of double‐ to single‐layered capillary conversion.